Pengaruh Terapi Murottal Al-Quran Surat Ar-Rahman Terhadap Kualitas Tidur Pada Lansia - Pebriana, Tanti; Nuryati, Elmi; Efendi, Rahmat (Jurnal Keperawatan Muhammadiyah, 2025)
Poor sleep quality is one of the disorders that often occur in the elderly, the impact of sleep disorders that the elderly often complain about is usually easy fatigue, dizziness, emotional disturbances or irritability, anxiety, tension and difficulty concentrating. Treatment of sleep quality disorders can be done with nonpharmacological treatments, one of which is Al-Qur'an murottal therapy. The purpose of this study was to determine the effect of murottal Al-Qur'an surah ar-rahman terapy to quality of sleep among elderly of panti sosial tresna werdha natar, lampung province 2024. The research design used in this study was Quasi Exsperimen with a one group pre post test approach with design. The population in this study were elderly people who were in the panti sosial tresna werdha natar with a total of 80 elderly people, the sample in this study were 22 respondents with purposive sampling technique. Data collection in this study used the PSQI questionnaire, SOP Al-Qur'an murottal therapy and observation sheets. Bivariate analysis using the T-dependent test. The results showed that the total number of respondents was 22 elderly, most of the respondents were 60-74 years old as many as 15 elderly (68.2%) while those aged 75-90 were 7 elderly (31.8%), the number of male gender was 10 elderly (45.5%) and female 12 elderly (54.5%). The conclusions of the study showedthat there was an effect of murottal Al-Qur'an surah ar-rahman terapy to quality of sleep among elderly of panti sosial tresna werdha natar, as evidenced by the results of the T- dependent test obtained the the averange value of sleep quality before and after the descreased from 10,36 to 4,05 with a p-value of 0.000.